Técnicas grafo plásticas en el desarrollo de la motricidad fina en los niños y niñas de 4 a 5 años de la unidad educativa “Nación Puruhá” Palmira, Guamote, período 2016. - Malán Guamán, Sara María (2017)
This research work is about Plastic graphical techniques in the development of fine motor skills in children between the ages of 4 and 5 years, it was carried out in the Educational Unit "Puruhá Nation" in Guamote Canton, during the school year 2016. The main objective is to apply plastic graphical activities the same ones that will motivate to perform a series of actions, movements and manual exercises that will allow extending the fine motor skills of the children. The content focuses on the variables that contain themes and subtopics that refer to plastic graphical techniques and the development of fine motor skills. The research process was based on a quasi- experimental design, the types of research focused on a field work and bibliographical, the method used is the hypothetical - deductive focused on general facts to reach particulars. As support for the research, we worked with 48 children, for that we used an observation sheet with data from which statistical tables and graphs were made, and then proceed to test the hypotheses; the alternative guidelines are structured in terms of exercises: shredding, wrinkling and dactyl painting. The results obtained were positive because the boys and girls reinforced their digital clamp, grip and eye-hand coordination, which, through exercises in plastic-graphical techniques, the children exercised coordinated movements and improved the fine motor necessary for prewriting processes; Finally, it was possible to achieve a manual oculus connection, improving the movements of the index finger and thumb in the handling of the digital clamp and improving manual exercises for the strengthening of fine motor skills.